High-dimensional immune phenotyping and transcriptional analyses reveal robust recovery of viable human immune and epithelial cells from frozen gastrointestinal tissue. Issue 6 (November 2018) - Konnikova, Liza; Boschetti, Gilles; Rahman, Adeeb; Mitsialis, Vanessa; Lord, James; Richmond, Camilla; Tomov, Vesselin; Gordon, Will; Jelinsky, Scott; Canavan, James; Liss, Andrew; Wall, Sarah; et al.
Abstract Simultaneous analyses of peripheral and mucosal immune compartments can yield insight into the pathogenesis of mucosal-associated diseases. Although methods to preserve peripheral immune cells are well established, studies involving mucosal immune cells have been hampered by lack of simple storage techniques. We provide a cryopreservation protocol allowing for storage of gastrointestinal (GI) tissue with preservation of viability and functionality of both immune and epithelial cells. These methods will facilitate translational studies allowing for batch analysis of mucosal tissue to investigate disease pathogenesis, biomarker discovery and treatment responsiveness.